Evaluation of the quality scoring system of hard red spring wheat using four different roller mills. Issue 1 (1st January 2018) - Baasandorj, Tsogtbayar; Ohm, Jae-Bom; Dykes, Linda; Simsek, Senay
ABSTRACT: Wheat quality laboratories need a scoring system for efficient segregation of wheat samples. A comprehensive and objective scoring system was developed to assist the evaluation of end-use quality of hard red spring (HRS) wheat. The overall quality score consisted of (1) wheat, (2) milling, (3) flour and dough, and (4) baking quality scores. Subscores attained from various quality tests were subdivided into individual categories. The objective of this experiment was to evaluate the quality scoring system. Since flour quality is highly influenced by experimental milling procedures, four different laboratory roller mills were compared for the scoring system using 12 HRS wheat samples. Although the mill type varied significantly ( p < 0.001) for the overall quality scores, they appeared to be consistent for ranking of wheat samples, showing significant correlation coefficients ( r ≥ 0.74, p < 0.01) between different mill types. Quad. Sr. mill was specifically identified to be more suitable for dough and bread-making quality evaluation of HRS wheat due to the higher consistency with a long-flow MIAG mill. The overall quality scores also showed a significant ( p < 0.001) variation among wheat samples, indicating that the scoring system could be useful to segregate HRS wheat samples for end users and breeders. Abbreviation: HRS: Hard Red Spring; MN: Minnesota; MT: Montana; ND: North Dakota; SD: South Dakota; OVA: Overseas Varietal Analysis; Quad: Quadrumat; AACCI: American Association of Cereal Chemist International; SKB: Sandstedt Kneen and Blish; SAS: Statistical Analysis System; ANOVA: Analysis of Variance; LSD: Least Significant Difference; ERE: Extensograph Resistance to Extension; SDS: Sodium Dodecyl Sulfate